Modelling and simulation for autonomous systems 6th International Conference, MESAS 2019, Palermo, Italy, October 29-31, 2019, revised selected papers /: 6th International Conference, MESAS 2019, Palermo, Italy, October 29-31, 2019, revised selected papers. (©2020) - Unknown
No abstract available